Analysis of Social Return On Investment (SROI) in the Community Empowerment Program Related to Integrated Agroculture for Forest Area Management in Trenggulunan Village, Pancur District, Rembang Regency - Jayadi Jayadi; Bambang Apriyanto; Edi Saputra; Vernando Pratama Putra; Mohammad Saddam Husen (Journal of World Science, 2025)
The Trenggulunan Agro View (TAV) Program addresses socio-environmental challenges around PLTU Rembang by leveraging social forestry, waste-to-value innovations (e.g., FABA fertilizer), and renewable energy (co-firing biomass) to empower communities. This study evaluates TAV’s socio-economic and environmental impact using SROI analysis, assessing its scalability for Indonesia’s energy transition. A qualitative-descriptive approach with SROI methodology (six stages) was applied, incorporating stakeholder interviews, financial data, and impact monetization (deadweight, displacement, attribution adjustments). The program yielded an SROI of 2.23, reflecting Rp2.23 social value per Rp1 invested, with tangible outcomes: 31% poverty reduction, 128.5% income growth, and 8% annual increase in village revenue. Environmental benefits included critical land restoration and EBT-based pest control. TAV demonstrates a replicable model for integrating CSR with renewable energy agendas, advocating policy support for scalable, community-driven forestry-energy synergies.